2017
DOI: 10.1104/pp.17.00298
|View full text |Cite
|
Sign up to set email alerts
|

KNOX Protein OSH15 Induces Grain Shattering by Repressing Lignin Biosynthesis Genes

Abstract: Seed shattering is an agronomically important trait. Two major domestication factors are responsible for this: qSH1 and SH5. Whereas qSH1 functions in cell differentiation in the abscission zone (AZ), a major role of SH5 is the repression of lignin deposition. We have determined that a KNOX protein, OSH15, also controls seed shattering. Knockdown mutations of OSH15 showed reduced seed-shattering phenotypes. Coimmunoprecipitation experiments revealed that OSH15 interacts with SH5 and qSH1, two proteins in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 51 publications
4
89
0
Order By: Relevance
“…A pattern of nonlignified cells next to lignified cells is important for a functional AZ in fruits of Arabidopsis thaliana and rice (Liljegren et al., , ; Rajani and Sundaresan, ; Mitsuda and Ohme‐Takagi, ; Zhou et al., ; Yoon et al., , ). However, our study found approximately equal numbers of species with and without differential lignification (8 vs. 9, respectively) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pattern of nonlignified cells next to lignified cells is important for a functional AZ in fruits of Arabidopsis thaliana and rice (Liljegren et al., , ; Rajani and Sundaresan, ; Mitsuda and Ohme‐Takagi, ; Zhou et al., ; Yoon et al., , ). However, our study found approximately equal numbers of species with and without differential lignification (8 vs. 9, respectively) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thin and nonlignified walls are more accessible for degradation, and differential lignification creates physical tension between cell types when tissue dries and loses turgor pressure, which eventually leads to breakage at the weakly attached AZ (Sexton and Roberts, ). Rice mutants with ectopic lignification in the AZ exhibit increased tensile strength of tissues holding the grain onto the plant and reduced or loss of grain abscission (Zhou et al., ; Yoon et al., , ; Lv et al., ). In fruit abscission (also called dehiscence) of Arabidopsis , mutants with ectopic lignification in the AZ (Rajani and Sundaresan, ) or nonlignification in the cells adjacent to the AZ (Liljegren et al., , ; Mitsuda and Ohme‐Takagi, ) both inhibit dehiscence, demonstrating the importance of differential lignification in the abscission process.…”
mentioning
confidence: 99%
“…In rice, two BEL1‐type homeobox genes, qSH1 and SH5 , which are closely related to Arabidopsis PNY and PNF , are required for formation of the abscission zone that promotes seed shattering (Konishi et al ., ; Yoon et al ., ). OSH15, a BP‐like KNOX‐type homeodomain protein, is also involved in this process through its formation of a heterodimer with qSH1 and SH5 (Yoon et al ., ). Recently, it has been reported in maize that mutations in the two BELL1‐LIKE HOMEOBOX (BLH) genes BLH12 and BLH14 , which are close homologs of PNY and PNF , cause abnormalities in internode patterning and vascular bundles anastomosis, in addition to indeterminate branch formation in the tassel (Tsuda et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The Co-IP assays were performed as reported earlier (Cho et al, 2016;Yoon et al, 2017). Briefly, fusion molecules were coexpressed in rice Oc cell protoplasts.…”
Section: Co-immunoprecipitation Assaymentioning
confidence: 99%
“…Transgenic plants expressing OsVIL2-Myc were used for ChIP analysis, as described previously (Yang et al, 2013;Yoon et al, 2017), with the anti-Myc monoclonal antibody (Cell Signaling; #2276) and the anti-H3K27me3 monoclonal antibody (Millipore; 07-449). The assays were performed as reported earlier (Haring et al, 2007).…”
Section: Chromatin Immunoprecipitation Analysismentioning
confidence: 99%